A noção do medo frente as manifestações religiosas afro-decendentes - Santos, Maria José dos (2009)
The aim of this research is to investigate the fear facing the african- Brazilian religions and their manifestations in front of Municipal School Escolinha do Dom, is an individual or collective dimension. Indeed, research has established a dialogue between the historical formation and development of religion of Candomblé and Umbanda understood in its plurality, seeking to study the fear inside of discussions fostered in the Municipal Network for Teaching of Recife, in this capacity in the Group of Relations Ethnic-racial as well as linking these discussions within the school environment, teachers and learners in practice.